New broad beam gas ion source for industrial application; Journal of Vacuum Science and Technology A; Vol. 14, № 3 - Gavrilov N. V.; Mesyats G. A. Gennady Andreyevich; Nikulin S. P.; Radkovskii G. V.; Elkind A.; Perry A. J.; Treglio J. R. (1996, 1996)
В фонде НТБ ТПУ отсутствует